Evaluation of a resource for people bereaved by suicide. - Hawton, K; Sutton, L; Simkin, S; Walker, D; Stacey, G; Waters, K; Rees, S (2012)
BACKGROUND: Self-help resources are an important means of supporting people bereaved by suicide. These require careful evaluation. AIMS: To evaluate the use and impact of Help is at Hand, a hardcopy and online booklet produced as part of England's suicide-prevention strategy. METHODS: Data were collected on numbers of copies distributed and online access, and on users' views about the resource through questionnaires, interviews, and a focus group. RESULTS: Large numbers of copies of Help is at Hand were obtained by a range of organizations, but far fewer directly by individuals, although the resource was extensively accessed online. Evaluation of individuals' responses to the resource was challenging. However, most respondents were very positive about the overall format and content and especially sections on experiencing bereavement and practical matters relating to the death. The main complaint was delay in gaining access to Help is at Hand. CONCLUSIONS: Evaluation of resources for people bereaved by suicide is difficult but worthwhile. Help is at Hand was largely well received. The main problem was with regard to individuals gaining access to it, especially at a time when they most needed it. Promotion of resources such as Help is at Hand needs to be prioritized.